2014
DOI: 10.1068/a46267
|View full text |Cite
|
Sign up to set email alerts
|

Is Your Commute Killing You? On the Mortality Risks of Long-Distance Commuting

Abstract: There is a general belief that expanding labour-market regions, triggered by increased commuting, have positive economic effects on individuals, firms, and society. Recently, however, scholars have reported possible negative outcomes related to health and well-being. Based on these findings, this study addresses the association between longdistance commuting, and mortality. Using longitudinal individual data from between 1985 and 2008, focusing on 55-year-olds in 1994, we model mortality through propensity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…For example, Ross and Zenou () and Van Ommeren and Gutiérrez‐i‐Puigarnau () point out that commuting leads to increased absenteeism, and authors such as Koslowsky, Kluger, and Reich (), Evans, Wener, and Phillips () and Kahneman, Krueger, Schkade, Schwarz, and Stone (), among others, show the negative psychological effects that commuting can induce by raising worker stress levels. Similarly, Gottholmseder, Nowotny, Pruckner, and Theurl (), Hämmig, Gutzwiller and Bauer (), Hansson, Mattisson, Björk, Östergren, and Jakobsson (), Roberts, Hodgson and Dolan (), Sandow, Westerlund and Lindgren () and Palomino and Sarrias (), explore other harmful effects of commuting on health, in dimensions such as obesity, insomnia and increased likelihood of accidents and mortality, among others. Many of these studies point to the existence of variables that moderate these effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Ross and Zenou () and Van Ommeren and Gutiérrez‐i‐Puigarnau () point out that commuting leads to increased absenteeism, and authors such as Koslowsky, Kluger, and Reich (), Evans, Wener, and Phillips () and Kahneman, Krueger, Schkade, Schwarz, and Stone (), among others, show the negative psychological effects that commuting can induce by raising worker stress levels. Similarly, Gottholmseder, Nowotny, Pruckner, and Theurl (), Hämmig, Gutzwiller and Bauer (), Hansson, Mattisson, Björk, Östergren, and Jakobsson (), Roberts, Hodgson and Dolan (), Sandow, Westerlund and Lindgren () and Palomino and Sarrias (), explore other harmful effects of commuting on health, in dimensions such as obesity, insomnia and increased likelihood of accidents and mortality, among others. Many of these studies point to the existence of variables that moderate these effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transportation and health researchers have thus considered traffic congestion exposure as a critical factor that influences individuals’ physical and mental health. For example, a number of studies revealed that higher exposure to traffic congestion may be associated with escalated heart rate and blood pressure [6,7], heightened urinary catecholamine (a stress-related hormone) [8], and negative health outcomes [9,10,11]. In addition to these physical tolls, studies have also shown that exposures to traffic congestion may be linked to psychological stress [12,13,14,15,16,17] and reduced well-being [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…To accurately assess the effects of traffic congestion exposures on human health, it is important to accurately measure individual exposures to traffic congestion. Specifically, in terms of measuring traffic congestion exposures, most previous studies used area-based aggregate data (e.g., [9,21,22]) or focused only on commuting trips (and thus disregarded non-commuting trips) (e.g., [11,18,19]). We argue that these approaches in previous research may lead to erroneous assessments of individual exposures to traffic congestion, which may in turn lead to erroneous evaluations of the health impacts of traffic congestion because they did not consider individuals’ unique activity-travel patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, commuting has been shown to be associated with increased heart rate and blood pressure (Novaco et al, 1979;Schaeffer et al, 1988). Further, commuting translates into shorter sleeping times and sleep disorders (Costa et al, 1988;Walsleben et al, 1999;Hansson et al, 2011), a lower social capital and participation (Mattisson et al, 2015), which has in turn been associated with health outcomes (Putnam, 2000;Lindström, 2004;Besser et al, 2008), negative mood (Gulian et al, 1989), emotional arousal (Hennessy and Wiesenthal, 1997), lower well-being and life satisfaction (Stutzer and Frey, 2008;Roberts et al, 2011;Olsson et al, 2013) as well as higher levels of workplace aggression (Hennessy, 2008), poor concentration levels (Matthews et al, 1991) and a higher risk of mortality (Sandow et al, 2014).…”
mentioning
confidence: 99%